Treatment of a wounded person with mine-explosive combined trauma, with damage to the lung, liver, right hepatic artery, development of arteriobiliary fistula, complicated by recurrent hemobilia - I. I. Dzidzava; A. V. Moiseenko; A. S. Pasichnik; N. A. Petrov; B. N. Kotiv; D. A. Granov; A. A. Polikarpov; S. A. Alent’yev; S. A. Soldatov; O. V. Barinov (Вестник хирургии имени И.И. Грекова)
Damage of hepatic arteries with the formation of arteriobiliary fistula is a life-threatening consequence of liver injuries and traumas. A clinical observation of successful application of endovascular technologies in the treatment of arteriobiliary fistula is presented.